DETERMINAN FAKTOR YANG MEMPENGARUHI KADAR ASAM URAT PADA LANSIA YANG MENDERITA ASAM URAT DI KABUPATEN TULUNGAGUNG: Determinant factors influencing uric acid levels in elderly people suffering from gout in Tulungagung Regency - Nizar, Angga Miftakhul; Zuniawati, Dewi (Jurnal Penelitian, 2023)
Older people are at high risk of developing metabolic diseases such as high uric acid. The ability to do a protein diet needs to be improved in gout sufferers. The purpose of this thesis is to determine the relationship between dietary compliance and uric acid levels in the elderly at the Elderly Posyandu at, Tulungagung in 2023. The design used in this study is a corelational analytic design with a cross sectional approach. The population of this study were all elderly people suffering from gout at the Elderly Posyandu, Srikaton Village, Ngantru District, Tulungagung Regency, totaling 34 elderly people. The research sample was all elderly people suffering from gout at the Elderly Posyandu, Srikaton Village, Ngantru District, Tulungagung Regency, totaling 34 elderly people. In this study the sampling technique is total sampling. The research instruments were observation sheets and questionnaires equipped with general research data. Data processing in the form of editing, coding, scoring, tabulating was analyzed using the Spearman rho test. Based on the results of the study, the value of ρ was obtained (0.000) with α (0.05), because ρ <α, then H1 is accepted, meaning that there is a relationship between dietary compliance and uric acid levels in the elderly at the Elderly Posyandu Tulungagung in 2023. It can be concluded that it is important for the elderly to comply with the diet to avoid excess uric acid levels. The inability of the elderly to control and maintain diet patterns is also complicated by the elderly where at that age there is a decrease in body function so that the regulation and balancing of the disposal of uric acid levels in the body is not good.